THE ROLE OF PROFESSIONAL ORGANIZATIONS IN EARLY CHILDHOOD EDUCATION POLICY IMPLEMENTATION IN EAST KALIMANTAN - Adharina Dian Pertiwi; Joko Pamungkas (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to examine the strategic role of professional associations in early childhood education policy implementation, focusing on HIMPAUDI East Kalimantan. Non-formal early childhood educators in developing regions face severe structural vulnerabilities, characterized by a substantial policy gap between central government expectations and local capacities, geographical isolation, and low digital literacy. Utilizing a descriptive qualitative design, this research gathered empirical data through in-depth interviews with the Regional Head of HIMPAUDI East Kalimantan and document analysis. The findings reveal that the association does not merely serve as a gathering platform but functions as a vital strategic partner for local governments. Through multi-layered communication, self-funded tiered training programs, and data-driven political lobbying, the association successfully translates rigid macro-regulations into applicable classroom practices while securing local financial incentives for marginalized educators. This community-based resilience mechanism effectively mitigates administrative burdens and compensates for local government bureaucracy delays. The study implies that local governments should transition toward a co-governance model by formally involving professional networks in policy formulation to ensure equitable educational quality in the new capital city (IKN) era.